Regulation of growth hormone messenger RNA by thyroid and glucocorticoid hormones. - Martial, J A (1977)
Thyroid and glucocorticoid hormones stimulate growth hormone synthesis in cultured rat pituitary cells (GC). We have compared changes in growth hormone production and mRNA in these cells. Triiodothyronine (10 nM) and dexamethasone (1 micron) stimulated increases in growth hormone production by 2.5- and 3.8-fold, respectively. There were corresponding increases in the capacity of RNA from hormone-treated cells to direct synthesis of pregrowth hormone in a wheat germ cell-free translation system, suggesting hormone-regulated increases in growth hormone mRNA. Hormone-induced changes in mRNA were also demonstrated by determining the kinetics of hybridization of a cDNA probe prepared from RNA enriched (about 70%) for growth hormone translational activity with RNA from control and hormone-treated cells. These results suggest that thyroid and glucocorticoid hormones can regulate growth hormone production by influencing the levels of its mRNA.